Pain Intensity, Headache Frequency, and the Behavioral Activation and Inhibition Systems. Issue 12 (December 2015) - Jensen, Mark P.; Tan, Gabriel; Chua, Shi Min
Abstract : Objectives: To test the hypothesized associations between measures of the behavioral inhibition system (BIS) and behavioral activation system (BAS) and both the intensity and frequency of pain. Methods: A total of 563 college students were administered measures of BIS and BAS and asked to indicate both (1) the average intensity of pain at 10 body sites during the past week and (2) the frequency with which they experience mild, moderate, and severe headaches. The associations between (1) the BIS and BAS scale scores and (2) the worst average pain intensity experienced and headache frequencies were examined using a series of 1-way analyses of variance. Results: As predicted, the measure of BIS demonstrated significant and nonlinear associations with both pain intensity and headache frequency. The measure of BAS was not significantly related to pain intensity, but did demonstrate a nonlinear association with the frequency of severe headaches. Discussion: The findings are consistent with predictions based on a model hypothesizing that pain has a nonlinear impact on both BIS and BAS, with a stronger impact on BIS than BAS. If the current results are replicated in other samples, including samples of individuals with chronic pain, they have important implications for identifying biological factors that could influence pain and behavioral responses to pain, as well as for the development and evaluation of treatments that could enhance positive treatment outcomes.